Penerapan media pembelajaran interaktif berbasis game wordwall untuk meningkatkan keaktifan dan hasil belajar siswa kelas V SDN 16 Padang Magek - Salsa Mutiara Ningsih; Sela Novsetia Prabeni; Salsabila Febrianti; Salsa Bila4 Bila; Susi Ratna Sari (Al-Azkiya: Jurnal Pendidikan MI/SD, 2026)
This research is motivated by the low level of student activity and learning outcomes in social studies learning in class V UPT SDN 16 Padang Magek which is still centered on the lecture method. This research aims to increase student activeness and learning outcomes through the application of Wordwall-based interactive learning media on biological wealth materials. The method used is Classroom Action Research (PTK) with a qualitative descriptive approach which is carried out in two cycles. The research subjects consisted of 24 students. Data were collected through observation and documentation techniques. The results of the study showed that the use of Wordwall was able to increase student activity, with 80% of students in the very active category. In addition, students' understanding of the material also increased, as seen from their ability to answer questions appropriately. This game-based media creates a more interesting, interactive, and fun learning atmosphere. Thus, the use of Wordwall has been proven effective in improving student engagement and learning outcomes in social studies lessons at elementary school.